Gender issues in a company operating in a female-dominated industry, using an audit as an example - Genrietta Soboleva; Ekaterina Zuga (Innovar: Revista de Ciencias Administrativas y Sociales)
This study investigates the gender issues prevalent in Russian companies where more than 80% of the workforce is female. The objective is to describe the existence and nature of gender-related challenges in industries with predominantly female employees, as well as to identify their underlying causes and potential consequences. Data for the study were gathered from audit firms and a sample survey of auditor salaries in Russia, which were statistically analyzed. The findings indicate that companies do not implement modern strategies or practices to address gender imbalances. Specifically, gender issues such as the "glass ceiling," wage gap, and unequal career advancement opportunities persist in the auditing sector. Although these companies report progress on various gender-related indicators in their public relations materials, the actual implementation of policies remains insufficient. To address these challenges, the scope of gender-related disclosures in corporate reports must be expanded, and broader academic discussions should be initiated. A limitation of the study is that it focuses solely on one profession, and the results should be validated in other comparable occupations. Furthermore, salary evaluations were conducted using indirect methods due to the lack of sufficient disclosure.